A Case of Paratyphoid Fever Accidentally Treated with Amoxycillin - I. Darmansjah (Indonesian Pediatric Society, 1974)
A case of paratyphoid-fever isreported below which respondeddramatically to 6 (D (-) -Amino-p-Hydroxyphenyl acetamido) - Penicil-lanic acid or amoxycillin, known inIndonesia under the trade name ofAmoxil (250 mg crupsules).